2020
DOI: 10.1186/s13059-020-1944-4
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Co-opted transposons help perpetuate conserved higher-order chromosomal structures

Abstract: Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…For instance, we identified an intronic STAT1 binding site derived from a primate-specific TE in the human DICER1 locus. While we did not uncover consistent evidence supporting IFNG-inducible regulation of human DICER1 , these observations align with the concept of convergent regulatory evolution, in which similar expression patterns are perpetuated by the co-option of lineage-specific TEs ( Choudhary et al, 2020 ; Sundaram et al, 2014 ). Therefore, as B2_Mm2 elements shaped the evolution of rodent immune regulatory networks, individual co-option events may have mediated either divergence or preservation of gene expression patterns.…”
Section: Discussionsupporting
confidence: 49%
“…For instance, we identified an intronic STAT1 binding site derived from a primate-specific TE in the human DICER1 locus. While we did not uncover consistent evidence supporting IFNG-inducible regulation of human DICER1 , these observations align with the concept of convergent regulatory evolution, in which similar expression patterns are perpetuated by the co-option of lineage-specific TEs ( Choudhary et al, 2020 ; Sundaram et al, 2014 ). Therefore, as B2_Mm2 elements shaped the evolution of rodent immune regulatory networks, individual co-option events may have mediated either divergence or preservation of gene expression patterns.…”
Section: Discussionsupporting
confidence: 49%
“…And 63 out of 64 sites for CTCF AID2/dZF10 decreased site cluster 5 could be assigned to LINE L1. It has been reported that LTR13/LTR41/LINE elements were associated with CTCF [ 49 ]. Our study confirmed this observation and further suggested specifical ZFs can be related to the individual transposable element type.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a direct effect on genes, some TFBS generated by TEs can affect the three-dimensional organization of chromatin and thus participate in the regulation of genes that are not in close proximity. This process is exemplified in mammals where many of the CTCF TFBS, which play an important role in the definition of topologically associated domains (TADs), are derived from TEs [182,183]. A similar effect of TEs on the spatial organization of the genome is found in plants where miniature inverted-repeat transposable elements (MITEs) are associated in rice and sorghum with the presence of matrix attachment regions, which serve as anchors for loops [184].…”
Section: The Impact Of Tes On Gene Regulationmentioning
confidence: 95%
“…Either through exaptation or positive selection on new insertions, TEs have been an important source of evolutionary novelties and have been instrumental in the evolution of biological processes that have affected the diversification of eukaryotes [283]. For instance, many of the traits that are responsible for the evolutionary success of mammals have been profoundly impacted by TEs, from placenta formation [182,202] to the evolution of a complex brain [199,284]. TEs could also affect the diversification of life by directly driving the formation of species [285,286].…”
Section: The Role Of Tes In the Diversification Of Lifementioning
confidence: 99%